Answer: The distance is d = 13 .
Step-by-step explanation:
In order to find the distance between the two points, you need the distance formula:
[tex]d = \sqrt{(x_{2} - x_{1})^2 +(y_{2} - y_{1})^2}[/tex] where there is [tex](x_{1}, y_{1})[/tex] and [tex](x_{2}, y_{2})[/tex] .
-Use the those two points [tex](6,-7)[/tex] and [tex](1,5)[/tex] for this formula:
[tex]d = \sqrt{(1 -6)^2 +(5 + 7)^2}[/tex]
-Then, you start solving:
[tex]d = \sqrt{(1 -6)^2 +(5 + 7)^2}[/tex]
[tex]d = \sqrt{(-5)^2 +(12)^2}[/tex]
[tex]d = \sqrt{25 +144}[/tex]
[tex]d = \sqrt{169}[/tex]
[tex]d = 13[/tex]
So, therefore, the result is [tex]d = 13[/tex] .